2004
DOI: 10.1074/jbc.m312442200
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42-dependent Mediation of UV-induced p38 Activation by G Protein βγ Subunits

Abstract: The beta and gamma subunits of heterotrimeric GTP-binding proteins (Gbetagamma) were found to bi-directionally regulate the UV-induced activation of p38 and c-Jun NH(2)-terminal kinase, and the UV-induced activation of p38 was reported to enhance the resistance of normal keratinocytes to apoptosis. However, the signaling pathway downstream of Gbetagamma for this UV-induced p38 activation is not known. Thus, we examined the role of the Rho GTPase family in the regulation of UV-induced p38 activation by Gbetagam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
1
30
0
2
Order By: Relevance
“…In animal cells, it has been shown that UV-B activates the Ga-Gbg complex to release free Ga and Gbg, both of which result in HB-EGF secretion and subsequent activation of the EGF signal transduction pathway (Seo et al, 2004(Seo et al, , 2007Seo and Juhnn, 2010), suggesting that both Ga and Gbg are functional units to transmit UV-B signaling. However, until now, whether G proteins participate in the responses of plant cells to UV-B was not known.…”
Section: Ga Plays An Important Role In Uv-b Guard Cell Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal cells, it has been shown that UV-B activates the Ga-Gbg complex to release free Ga and Gbg, both of which result in HB-EGF secretion and subsequent activation of the EGF signal transduction pathway (Seo et al, 2004(Seo et al, , 2007Seo and Juhnn, 2010), suggesting that both Ga and Gbg are functional units to transmit UV-B signaling. However, until now, whether G proteins participate in the responses of plant cells to UV-B was not known.…”
Section: Ga Plays An Important Role In Uv-b Guard Cell Signalingmentioning
confidence: 99%
“…However, few of the molecular players involved in UV-B signal transduction are currently known. In mammalian cells, heterotrimeric G proteins have been shown to mediate various UV-B-induced cellular responses, such as secretion of heparin-binding epidermal growth factor (HB-EGF), activation of mitogen-activated protein kinases, cyclooxygenase2 expression, and apoptosis in human keratinocytes (Seo et al, 2004(Seo et al, , 2007Seo and Juhnn, 2010), suggesting that G proteins are important molecular players in UV-B signal transduction. However, at present, whether G proteins participate in the responses of plant cells to UV-B is not known.…”
mentioning
confidence: 99%
“…To this end, CDC42 that showed very high over-expression in HN + PTC compared to MNG merits further discussion. CDC42 is activated by some environmental factors such as gamma-radiation or UVB-light [13,14]. None of our patients had a documented history of medical or obvious environmental exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Trabalhos recentes têm demonstrado também um possível papel na resposta ao dano no DNA. Foi observado que os níveis de Cdc42 ativada aumentam após o tratamento com UVC e Cdc42 é capaz de ativar p38 (Seo et al, 2004). Alguns trabalhos mostram que Cdc42 pode estar relacionado com o envelhecimento (Kerber et al, 2009;Wang et al, 2007;Florian et al, 2012) e que esta proteína pode promover a senescência de modo dependente de P53 (Wang et al, 2007).…”
Section: Discussionunclassified
“…Seo e colaboradores observaram que Cdc42 é ativado em células COS-1 tratadas com radiação UVC e foi observado também que Cdc42 promove a ativação de p38 induzida por UV (Seo et al, 2004) Analisando a porção C-terminal de Cdc42 foi identificado uma possível sequência sinal de localização nuclear (NLS) (Williams, 2003) e, recentemente, foi descoberta a translocação de Cdc42 para a membrana nuclear após o estresse de células fotorreceptoras por exposição excessiva à luz (Heynen et al, 2011).…”
Section: Cell Division Cycle 42 (Cdc42)unclassified